Exploring and exploiting cuticle biosynthesis for abiotic and biotic stress tolerance in wheat and barley - Wang, Xiaoyu; Chang, Cheng (Frontiers in Plant Science, 2022)
Wheat and barley are widely distributed cereal crops whose yields are adversely affected by environmental stresses such as drought, salinity, extreme temperatures, and attacks of pathogens and pests. As the interphase between aerial plant organs and their environments, hydrophobic cuticle largely consists of a cutin matrix impregnated and sealed with cuticular waxes. Increasing evidence supports that the cuticle plays a key role in plant adaptation to abiotic and biotic stresses, which could be harnessed for wheat and barley improvement. In this review, we highlighted recent advances in cuticle biosynthesis and its multifaceted roles in abiotic and biotic stress tolerance of wheat and barley. Current strategies, challenges, and future perspectives on manipulating cuticle biosynthesis for abiotic and biotic stress tolerance in wheat and barley are discussed.